2016
DOI: 10.1097/ta.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis among critically ill combat casualties

Abstract: Prognostic and epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Similarly, Sharp et al [ 3 ] found that an elevated serum CK value was a significant risk factor for AKI. Studies performed in war fighters have confirmed this association and have reported a positive correlation between AKI stages and higher CK values [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, Sharp et al [ 3 ] found that an elevated serum CK value was a significant risk factor for AKI. Studies performed in war fighters have confirmed this association and have reported a positive correlation between AKI stages and higher CK values [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 83%
“…This result suggests a biologic gradient between worse renal function and mortality [ 24 , 33 ] and that the chances of death are proportional to the severity of AKI. Although we did not analyze the predictors of mortality in our series, it is important to mention the study by Stewart et al [ 15 ]. They examined a large cohort of combat casualties to identify risk factors for rhabdomyolysis and its relation to AKI and death.…”
Section: Discussionmentioning
confidence: 92%
“…Our study supports evidence from previous observations. AKI has been reported to be associated with higher mortality in patients with all-cause and combat-injury-induced rhabdomyolysis [ 30 , 31 ]. Another important finding was that AKI is independently associated with the increased requirement of mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed recognition and treatment of sepsis; the unavailability of diagnostics tools or a higher level of care; limited access to antivenom and antibiotics, including highly active antiretroviral therapy; and the inability to provide timely and monitored management of hyperkalemia, acidosis, and fluid overload with diuretics increase AKI incidence, likely escalate the requirements for dialysis treatment, and lead to higher mortality. 13 , 14 Tropical infections, 16 , 21 community-acquired pneumonia or meningitis, pregnancy-related complications (bleeding, eclampsia, septic abortion), 22 , 23 , 24 , 25 , 26 dehydration due to inadequate access to fluids in frail older adults and young children, exposure to nephrotoxins (e.g., nonsteroidal anti-inflammatory drugs, calcineurin blockers, antiretroviral therapy, antibiotics, or contrast media), 27 , 28 , 29 poisons (e.g., arsenic poisoning), 30 drug interactions (e.g., calcium-channel blocker plus clarithromycin), 31 animal venoms (e.g., snake venom), 20 trauma-induced rhabdomyolysis, 32 and shock states due to heart failure, hypovolemia, or sepsis 1 , 16 , 33 are all factors that can result in AKI. AKI following polypharmacy and nephrotoxin exposures in developing countries may be more prevalent, particularly when oversights of pharmacies are not robust due to more limited resources.…”
Section: Methodsmentioning
confidence: 99%